Yes-Associated Protein (YAP) Promotes Tumorigenesis in Melanoma Cells Through Stimulation of Low-Density Lipoprotein Receptor-Related Protein 1 (LRP1). Issue 1 (December 2017) - Xiong, Huizi; Yu, Qian; Gong, Yu; Chen, Wenjuan; Tong, Yunlei; Wang, Yao; Xu, Hui; Shi, Yuling
Abstract YAP is a critical protein in cancer development and can induce transformative phenotypes in mammary epithelial cells. Previous studies have provided evidence that YAP can contribute to the metastatic behavior of melanoma, since specific knockdown of YAP leads to reduced metastatic and invasive capacityin vitro . However, the mechanism by which YAP regulates the function of melanoma is unknown. Here, we identified that YAP has a positive impact on the expression of LRP1, which also plays critical roles in cancer. Mechanically, knockdown of YAP resulted in a significant down-regulation of LRP1 at both the protein and mRNA levels. Tissue microarray analysis (TMA) also showed a positive correlation between YAP and LRP1 expression. In addition, reduction of YAP-impaired pro-carcinogenic phenotypes could be partially reversed by simultaneous overexpression of LRP1, suggesting that LRP1 is functionally important in YAP-induced melanoma tumorigenesis. Furthermore, we found that LRP1 was regulated by YAP through a transcription- and promoter-dependent mechanism. Taken together, our results suggest that YAP regulates LRP1 through stimulation of the LRP1 promoter and that LRP1 may be an important target for influencing YAP in melanoma.